Pengaruh Komik sebagai Media Promosi Kesehatan terhadap Peningkatan Pengetahuan Siswa Sekolah Dasar: Sebuah Kajian Pustaka - Luthfiana Nur (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Comics is one of the learning media that has many advantages, and close indentik with children. Comics also has the potential to be a health promotion media because the comics are assessed to increase the knowledge of readers. Many researchers have built and comic effectiveness as a health promotion promotion. This article was prepared using literature study. The purpose of writing this article is to summarize the findings and evidence that have been produced by researchers who have conducted research on the influence of comics on improving the health knowledge of elementary school students. Electronic databases are used as the main source of searches with the keywords